DIALEKTIKA AGAMA DAN BUDAYA: MUNGKINKAH BERTEMU? Sebuah Kajian Sosio-Antropologi tentang Agama Teks dan Agama Masyarakat - Roibin . (Studia Philosophica et Theologica, 2008)
Human belief that leads to view nature and ancestral spirits as gods (natural mythology and animism), and to regard things of magical power (dynamism), cannot indeed be evoided. Even if their religious belief is profound, they still conceive that such a behavior (to believe natural mythology) does not mean polytheism or syirik, because the one God is not denied. Therefore, people can still worship natural things such as plants, idols, mysterious gods, holy persons regardless of they Islamic religious belief. People worship whatever they experience as things extraordinary. But actually in the deep of their heart, they can still distinguish that such a worship is an expression of religious belief or not. Courage to worship the true God is definitely a possibility to be discovered by human being. This article will explore dialectic relationship between religion and culture. Can religion and culture meet and go dialogically together in a socio-anthropological-religious convergence? This is the status questionis of the study.